Propagação larval pós-alimentar de Lucilia sericata (Meigen, 1826) (Diptera: Calliphoridae) em arena circular - Pires, Sabrina Medeiros (2007)
The blowflies are the first insects to compose the faunistic succession of human cadavers, thus helping to determine the postmortem interval (PMI). However, failing to consider larval post-feeding dispersal can compromise medical-criminal inquiries. In order to investigate the relationship between post- feeding Lucilia sericata larvae and their weight, radial dispersion and depth, an artificial arena was built simulating the natural environment. We observed a difference in mean pupal weight between males (30.28mg) and females (32.35mg). We also observed that the majority of pupae were recovered a distance of 33 to 45cm from the center of the arena, and at a depth of 6 to 8cm from the surface. However, we observed no differences in radial dispersion and depth of pupation between males, females or unviable individuals. Correlation analysis between weight and distance (r = 0.246) and between weight and depth (r = 0.321) was directly proportional, suggesting that heavier pupae dispersed farther and deeper than lighter pupae. The experiment also allowed us to conclude that a circular arena permitted larval dispersion all directions.